KARAKTERISTIK HABITAT TRENGGILING JAWA (MANIS JAVANICA) DI TAMAN NASIONAL GUNUNG HALIMUN SALAK - Afroh Manshur; Agus Priyono Kartono; Burhanuddin Masy'ud (Media Konservasi, 2015)
Pangolin (Manis javanica) is one of the critically endangered mammals that categorized by International Union for Conservation of Nature. Conservation efforts for M. javanica still limited caused of it’s ecological study has not been revealed. Therefore, the objective of this study was to determine the characteristics of M. javanica’s habitat The determination of measuring habitat using single plot based on the presence of M. javanica in a location that known by exploration method and open grid technique according the identification of footprint. M. javanica using a habitat which 9 special components that grouped into 6 the main character, namely: (1) The above canopy’s density is high category, (2) the number of plant species that used as digs of it’s prey is rarely category, (3) A source of feed is very close around the M. javanica’s den, (4) there is no competitors and predators around the M. javanica’s den, (5) a very steep slope steepness and (6) the soil’s texture is medium categorized. Chisquare test showed that M. javanica didn’t use a site as it’s habitats despite having the appropriate characteristics, if there are competitors in those area.  Keyword : anti-predator, competition, life strategies, Pholidota, thermoregulation